Identification of FadAB Complexes Involved in Fatty Acid β-Oxidation in Streptomyces coelicolor and Construction of a Triacylglycerol Overproducing strain - Menendez-Bravo, Simón; Paganini, Julián; Avignone-Rossa, Claudio; Gramajo, Hugo; Arabolaza, Ana (Frontiers in Microbiology, 2017)
Oleaginous microorganisms represent possible platforms for the sustainable production of oleochemicals and biofuels due to their metabolic robustness and the possibility to be engineered. Streptomyces coelicolor is among the narrow group of prokaryotes capable of accumulating triacylglycerol (TAG) as carbon and energy reserve. Although the pathways for TAG biosynthesis in this organism have been widely addressed, the set of genes required for their breakdown have remained elusive so far. Here, we identified and characterized three gene clusters involved in the β-oxidation of fatty acids (FA). The role of each of the three different S. coelicolor FadAB proteins in fatty acid catabolism was confirmed by complementation of an E. coliΔfadBA mutant strain deficient in β-oxidation. In S. coelicolor, the expression profile of the three gene clusters showed variation related with the stage of growth and the presence of FA in media. Flux balance analyses using a corrected version of the current S. coelicolor metabolic model containing detailed TAG biosynthesis reactions suggested the relevance of the identified fadAB genes in the accumulation of TAG. Thus, through the construction and analysis of fadAB knock out mutant strains, we obtained an S. coelicolor mutant that showed a 4.3-fold increase in the TAG content compared to the wild type strain grown under the same culture conditions.